Exploratory walks as an example of networking research = Spacery badawcze jako przykład badań sieciujących - Kwiatkowski, Mariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article concerns the author`s concept of a specific kind of social research. "Networking research" rely on connecting field work research with the intention of making social change. The aim of the networking research is "networking",ie. the strengthening of interpersonal relations, inter-organizational and cross-sector relations in the local community.
Keywords: action research; cross-linking studies; research "walk & talk"; revitalization; participations; badania w działaniu; badania sieciujące; badania "walk & talk"; rewitalizacja; partycypacja